Variation of address terms in Malay : case study of Malay families in Singapore - Siti Nadiah Mohd Shafie Maskon (2014)
The usage of address terms in Malay conversations is an important feature of politeness as it is determined by the relative age difference, power status and social distance between the interlocutors. This paper examines the use of address terms among the members of four Malay families in Singapore. Using recordings of natural conversations as data, this study investigates how address terms are used among the family members. The findings of this study confirm that there is a hierarchical system in Malay address term usage. This hierarchy is defined by pragmatic conventions that determine the polite way to address a particular person. Shifts in address terms are also observed in the conversations. Since the age difference, power status and social distance between speaker and addressee are constants in the family domain, these variations in address terms are attributed to factors that arise during the interaction, such as the content of the conversation, stance taken and changes in the relationship between interlocutors. The variations come in different forms; a switch from one address term to another, use of zero-reference and use of indirect address terms. It is argued that factors such as the structure of the Malay language, the speaker’s dynamic assessment of the ongoing conversation and their awareness of the politeness criteria in Malay speech influence these shifts.